Pressure-dependent bond stress-slip model for sand-coated FRP-concrete interface. (1st May 2021) - Lin, Hongwei; Feng, Peng; Yang, Jia-Qi
Highlights: The sand-coated FRP-concrete interface under confinement has two-stage response. Lateral confinement can improve mechanical properties of sand-coated interface. A pressure-dependent bond stress-slip model for sand-coated interface is developed. Abstract: The natural bond between FRP (fiber reinforced polymer) profile and concrete is quite weak, additional measures for improving the FRP-concrete interface should be taken to ensure the hybrid FRP-concrete members work compositely. There are several methods for interface improvement, and this paper focuses on the sand-coating method. Experimental tests including pull-out tests and push-out tests were conducted on sand-coated FRP-concrete interface. Test results revealed that the interfacial behavior included two stages. In the first stage, the concrete surrounding the plate failed in shear, which was similar to the adhesive bonding FRP-concrete interface. In the second stage, interfacial dilatation was induced and significant friction took place between fractured concrete surfaces. The adhesive-FRP interface and adhesive-sand aggregates interface were further damaged. Based on test results and numerical analysis, the variation of the interfacial dilatation and friction coefficient with the interfacial slip were determined. Finally, a pressure-dependent bond stress-slip model which was suitable for both active and passive confinement conditions was developed. This model can be implemented into commercial FE software and used for FE analysis of structural members. Comparisons with test results of the present paper and those from the literature indicate that the proposed model can provide reliable predictions.